Polymorphism of dna repair gene XPD Lys751Gln and chromosome aberrations in lymphocytes of thyroid cancer patients exposed to ionizing radiation due to the chornobyl accident - Shkarupa, V.M.; Mishcheniuk, O.Y.; Henyk-Berezovska, S.O.; Palamarchuk, V.O.; Klymenko, S.V. (Experimental Oncology, 2016)
The aim of this work was to analyze the relationship between polymorphisms of DNA repair gene XPD Lys751Gln and frequency and spectrum of chromosome aberrations in the culture of peripheral blood lymphocytes of thyroid cancer (TC) patients having been exposed to ionizing radiation due to the Chornobyl accident. Materials and Methods: XPD Lys751Gln polymorphisms were detected by polymerase chain reaction in 102 TC patients including 38 patients exposed to ionizing radiation due to Chornobyl disaster (Chornobyl recovery workers, evacuees, and the residents of contaminated areas), 64 patients without history of ionizing radiation exposure and 45 healthy residents of Ukraine as control group. Results: In homozygous carriers of the minor allele XPD Gln751Gln, exposed to ionizing radiation, the significantly increased risk of TC (odds ratio = 3.66; p = 0.03; 95% confidence interval 1.04–12.84) was found. Among evacuees and residents of contaminated areas, homozygous carriers of the minor allele variants of XPD gene were characterized by the high level of spontaneous chromosome aberrations. TC patients without history of ionizing radiation exposure, being homozygous carriers of the allele XPD Lys751Lys, had significantly reduced frequency of chromosome-type aberrations. Conclusions: The carriage of homozygous minor allele of DNA repair gene XPD Gln751Gln is a risk factor for TC in persons from Ukrainian population exposed to ionizing radiation and is associated with the increased levels of chromosomal instability. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.